EVOLVING PROFILE OF PANCASILA STUDENTS THROUGH THE MERDEKA CURRICULUM IN THE ERA OF 5.0 - Maghfirah, Naily Inayatul; Masrur, Irfan (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
This research explains the application of Merdeka Curriculum in developing profile of Pancasila students in early childhood at RA Al-Falah, Tenggarang, Bondowoso in the 2023/2024 academic year. Merdeka Curriculum gives students the freedom to develop their creativity, intelligence and character by paying attention to Pancasila values. as the basis of the Indonesian state. This research focuses on implementing the independent curriculum by developing the profile of Pancasila students. This research uses a qualitative descriptive method involving observation, interviews and documentation. The research results show that the implementation of Merdeka Curriculum has been successful in developing profile of Pancasila students. This curriculum facilitates children to learn actively and creatively through exploration, play, creativity and communication activities. In its implementation, Merdeka Curriculum is integrated with the learning of Pancasila values: mutual cooperation, honesty, tolerance, justice and love of the country. Children are taught about the meaning and importance of Pancasila values through stories, role plays and interactive classroom activities. Merdeka Curriculum learning process also encourages the development of children's character, such as self-confidence, responsibility, empathy and social intelligence. Children are invited to respect differences, help each other, and participate in group activities. The implementation of Merdeka Curriculum at RA Al-Falah is effective in developing the profile of Pancasila students in early childhood. This curriculum provides opportunities for children to grow and develop holistically, by strengthening understanding and appreciation of the values of Pancasila as the foundation of life in society, nation and state.